Prose fiction : an introduction to the semiotics of narrative - Ribó, Ignasi, 1971-; Open Book Publishers; BC Open Textbook Project; BCcampus (Open Book Publishers, 2019)
"This concise and highly accessible textbook outlines the principles and techniques of storytelling. It is intended as a high-school and college-level introduction to the central concepts of narrative theory that will aid students in developing their competence not only in analyzing and interpreting short stories and novels, but also in writing them. Prose Fiction prioritizes clarity over intricacy of theory, equipping its readers with the necessary tools to embark on further study of literature, literary theory and creative writing. Building on a "semiotic model of narrative," it is structured around the key elements of narratological theory, with chapters on plot, setting, characterisation, and narration, as well as on language and theme. The chapter on language constitutes essential reading for those students unfamiliar with rhetoric, while the chapter on theme draws together significant perspectives from contemporary critical theory (including feminism and postcolonialism)"--BC Campus website.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Includes bibliographical references.
Description based on online resource; title from pdf title page (viewed on March 2, 2020).
Keywords: Narration (Rhetoric); Storytelling -- Technique; Electronic books